Direct intranigral injection of dopaminochrome causes degeneration of dopamine neurons - Touchette, Jillienne C. (Neurosci Lett, 2015)
Parkinson's disease (PD) is characterized by progressive neurodegeneration of nigrastriatal dopaminergic neurons leading to clinical motor dysfunctions. Many animal models of PD have been developed using exogenous neurotoxins and pesticides. Evidence strongly indicates that the dopaminergic neurons of the substantia nigra pars compacta (SNpc) are highly susceptible to neurodegeneration due to a number of factors including oxidative stress and mitochondrial dysfunction. Oxidation of DA to a potential endogenous neurotoxin, dopaminochrome (DAC), may be a potential contributor to the vulnerability of the nigrostriatal tract to oxidative insult. In this study, we show that DAC causes slow and progressive degeneration of dopaminergic neurons in contrast to 1-methyl-4-phenylpyridinium (MPP(+)), which induces rapid lesions of the region. The DAC model may be more reflective of early stresses that initiate the progressive neurodegenerative process of PD, and may prove a useful model for future neurodegenerative studies.